1993
DOI: 10.1002/ijc.2910530205
|View full text |Cite
|
Sign up to set email alerts
|

The value of the 1981 who histological classification in inter‐observer reproducibility and changing pattern of lung cancer

Abstract: A series of 722 lung carcinomas, surgically resected and typed some years ago according to the 1967 WHO classification, was independently reviewed by 2 observers in order to test the reproducibility of histopathological typing when using the criteria of the 1981 WHO classification. Typing was fully agreed upon in 87% of cases. Agreement was very high for squamous-cell, small-cell and adeno-carcinomas (kappa = 0.87, 0.89 and 0.85, respectively) while adenosquamous (kappa = 0.56) and large-cell (kappa = 0.71) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 11 publications
3
19
0
1
Order By: Relevance
“…Consitent with other reports (22), in the present study, low levels of 5-hmC were more common in patients with lymph node metastases, high histological types and large tumor sizes, which are recognized prognostic factors for lung cancer (23). The proportion of low 5-hmC level in NSCLC patients with lymph node metastases was markedly higher than those patients without lymph node metastases, as well as the histological types and tumor sizes.…”
Section: -Hmc Level ---------------------------------------------------supporting
confidence: 83%
“…Consitent with other reports (22), in the present study, low levels of 5-hmC were more common in patients with lymph node metastases, high histological types and large tumor sizes, which are recognized prognostic factors for lung cancer (23). The proportion of low 5-hmC level in NSCLC patients with lymph node metastases was markedly higher than those patients without lymph node metastases, as well as the histological types and tumor sizes.…”
Section: -Hmc Level ---------------------------------------------------supporting
confidence: 83%
“…34) A pathological review study in Italy found that this change in criteria resulted in a 15% increase of adenocarcinoma and an 11% decrease of squamous cell carcinoma in proportion. 41) We are now conducting a similar pathological review study in two major hospitals in Osaka, which cover approximately 20% of all lung cancer cases in Osaka. Preliminary results showed that the impact of this change was not as signifi- cant as expected, and may not exceed 4% difference in the proportion of each histologic type in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the agreement between independent histological evaluations of lung cancer varies by calendar time, distribution of ''true'' histological types and edition of WHO classification (1967 versus 1981) [15,17]. Butler et al showed that the overall agreement of histological evaluations of lung cancer in New Mexico was lower for 1970-72 as compared to 1980-81.The rate of confirmation of large-cell carcinoma was lower when the proportion of large-cell carcinoma became larger in the more recent period [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the diagnostic agreement in the histopathological evaluation of lung cancer tissue have been performed in the past [8][9][10][11][12][13][14][15][16][17][18]. Only very few studies have been performed that compared the agreement of histological lung cancer diagnosis of an unselected population-based lung cancer case series and an independent pathology review [3,12,15,18].…”
Section: Introductionmentioning
confidence: 99%